Detection of EGFR Activating and Resistance Mutations by Droplet Digital PCR in Sputum of EGFR-Mutated NSCLC Patients. (February 2021) - Hackner, Klaus; Buder, Anna; Hochmair, Maximilian J; Strieder, Matthaeus; Grech, Christina; Fabikan, Hannah; Burghuber, Otto C.; Errhalt, Peter; Filipits, Martin
Background: Proof of the T790M resistance mutation is mandatory if patients with EGFR -mutated non-small cell lung cancer (NSCLC) progress under first- or second-generation tyrosine kinase inhibitor therapy. In addition to rebiopsy, analysis of plasma circulating tumor DNA is used to detect T790M resistance mutation. We studied whether sputum is another feasible specimen for detection of EGFR mutations. Methods: Twenty-eight patients with advanced EGFR -mutated NSCLC were included during stable and/or progressive disease. The initial activating EGFR mutations (exon 19 deletions or L858R mutations) at stable disease and at progressive disease (together with T790M) were assessed in simultaneously collected plasma and sputum samples and detected by droplet digital polymerase chain reaction (ddPCR). Results: Activating EGFR mutations were detected in 47% of the plasma samples and 41% of sputum samples during stable disease, and in 57% of plasma samples and 64% of sputum samples during progressive disease. T790M was detected in 44% of the plasma samples and 66% of the sputum samples at progressive disease. In ddPCR T790M-negative results for both specimens (plasma and sputum), negativity was confirmed by rebiopsy in 5 samples. Concordance rate of plasma and sputum for T790M was 0.86, with a positive percent agreement of 1.0 and a negative percent agreement of 0.80. Conclusions: We demonstrated that EGFR mutation analysis with ddPCR is feasible in sputum samples. Combination of plasma and sputum analyses for detection of T790M in NSCLC patients with progressive disease increases the diagnostic yield compared with molecular plasma analysis alone.